Analysis of ethnoscience integrated environmental literacy for junior high school - S. Solheri; Minda Azhar; Y. Yohandri (University of Muhammadiyah Malang, 2022)
An analysis of environmental literacy that integrates ethnoscience in sustainable science learning between scientific knowledge and problems in life, as well as the value of local wisdom. This study was aimed to determine the profile of ethnoscience integrated environmental literacy. This research uses a survey method with a sampling technique of cluster random sampling and conducting a Question Test and a Middle School Environmental Literacy Survey (MSELS) to students. The parameters of this study consist of knowledge of ecology, cognitive skills, attitudes and behavior. Descriptive data analysis used average score. Research findings indicate that the ethnoscience integrated environmental literacy of junior high school students obtained an average score of 61 (with a range of 100). The achievement of environmental literacy parameters for ecological knowledge, cognitive skills, attitudes and behavior are 48, 29, 73 and 71, respectively, while the results of the ethnoscience integrated environmental literacy analysis illustrate that the average Junior High School has implemented ethnoscience integration in environmental literacy well. So empowering knowledge and attitudes contribute to environmental literacy students.